PERAN GOOD CORPORATE GOVERNANCE DALAM PENGENDALIAN MANAJEMEN LABA: STUDI PADA PERUSAHAAN SEKTOR BASIC MATERIALS DI BURSA EFEK INDONESIA - Nuryanasari, Erin Prima; Fauzan (JURNAL ILMIAH EDUNOMIKA, 2025)
This study aims to evaluate the influence of institutional ownership, managerial ownership, independent boards of commissioners, and audit committees on earnings management practices in basic materials sector companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. Purposive sampling, a quantitative approach, yielded a sample of 183 companies. Data were obtained from annual reports and analyzed using multiple linear regression. The results indicate that institutional ownership has no significant effect on earnings management, suggesting suboptimal oversight by institutional shareholders. In contrast, managerial ownership contributes to reducing earnings management through the alignment of interests between management and shareholders. The independent board of commissioners helps mitigate earnings management by executing an objective supervisory function. However, the Audit Committee does not significantly affect earnings management, possibly due to inadequate execution of its oversight role. This research contributes to the literature on corporate governance and financial reporting and highlights the importance of strengthening internal monitoring mechanisms to enhance the transparency and accountability of financial statement. Keywords : Earnings Management, Institutional Ownership, Managerial Ownership, Independent Board Of Commissioners, Audit Committee.